Nonenzymatic addition of glucocorticoids to lens proteins in steroid-induced cataracts. - Manabe, S (1984)
A frequent manifestation of long-term glucocorticoid administration is the occurrence of posterior subcapsular cataracts. The molecular basis for this effect has not yet been elucidated. The addition of prednisolone to the rat lens in culture results in a time- and concentration-dependent lens opacification that correlates with the formation of covalent prednisolone-lens protein adducts. Prednisolone adduct formation was analyzed by [3H]prednisolone incorporation and by immunoprecipitation with antiserum specific for proteins modified by the nonenzymatic addition of prednisolone. In the rat lens, these adducts were localized in both the water-soluble and urea-soluble lens protein fractions. Gel electrophoresis and fluorography revealed that the most extensively modified proteins were two crystallins subunits. Lens proteins from 33 normal and cataractous human lenses were fractionated and analyzed for the presence of prednisolone-protein adducts by competitive radioimmunoassay. Adducts were detected only in those samples derived from glucocorticoid-induced cataractous lenses. We conclude that elevated glucocorticoid levels lead to the formation of glucocorticoid-lens protein adducts both in vitro and in vivo. Lens protein modification by glucocorticoids may lead to sufficient biochemical or structural alterations so as to result in cataract formation. The ability of glucocorticoids to form adducts with proteins in vivo also may play a role in some of the other toxic manifestations of long-term glucocorticoid therapy.